Hubungan Kesejahteraan Spiritual dengan Death Anxiety pada Pasien Paliatif : Literatur Review - Eriyani, Theresia; Shalahuddin, Iwan; Pebrianti, Sandra; Maulana, Indra (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Patients with terminal illness have a poor prognosis of illness and lead to death. The patient's understanding of the limited time he has makes the patient experience anxiety about death. Anxiety about death is specifically divided into anxiety about death itself and anxiety about the process of death. The purpose of this Literature Review is to determine and examine the spiritual qualities of death anxiety in palliative patients. In this study, the authors used literature review in the form of articles with research methods Randomized Control Trials (RCTs), cross sectional, sequential mixed, descriptive-correlational, and literature review to explore the effect of spiritual approaches on reducing anxiety levels of palliative patients using Narrative Review as the basis for reporting items of this literature review. Spiritual well-being is taken into account as an effective factor of satisfaction with life. The results also showed a significant negative association between spiritual well-being and death anxiety. Spiritual well-being can affect death anxiety in individuals, especially the elderly suffering from cancer. Individuals with higher spiritual well-being may experience less death anxiety, which stems from belief in a higher power that is God and in other worlds that can make death easy. Patients who had spiritual well-being and religious attitudes had a significant effect on life satisfaction, peace and mental health, and also reduced death anxiety. Spiritual coping and religiosity can affect the improvement of the quality of life of palliative patients with spiritual activity. Keywords: Spiritual Well-being, Death Anxiety, Palliative Patients  ABSTRAK Penderita dengan Terminal illness memiliki prognosis penyakit yang buruk dan berujung pada kematian. Pemahaman penderita akan keterbatasan waktu yang dimilikinya membuat penderita mengalami kecemasan akan kematian. Kecemasan akan kematian secara spesifik terbagi ke dalam kecemasan akan kematian itu sendiri dan kecemasan akan proses kematian. Tujuan Literatur Review ini adalah untuk untuk mengetahui dan menelaah mengenai kualitas spiritual terhadap death anxiety pada pasien paliatif. Pada penelitian ini, penulis menggunakan literature review berupa artikel-artikel dengan metode penelitian Randomized Control Trials (RCTs), cross sectional, sequential mixed,  descriptive-correlational, dan literature review untuk mengeksplorasi efek pendekatan spiritual pada penurunan tingkat kecemasan pasien paliatif menggunakan Narrative Review sebagai dasar untuk item pelaporan literatur review ini. Kesejahteraan spiritual diperhitungkan sebagai faktor kepuasan yang efektif dengan kehidupan. Hasil penelitian juga menunjukkan hubungan negatif yang signifikan antara kesejahteraan spiritual dan kecemasan kematian. spiritual well-being mampu mempengaruhi kecemasan kematian pada individu, khususnya lansia yang menderita kanker. Pada individu dengan kesejahteraan spiritual yang lebih tinggi mungkin mengalami kecemasan kematian yang lebih sedikit, yang berasal dari kepercayaan pada kekuatan yang lebih tinggi yaitu Tuhan dan di dunia lain yang dapat membuat kematian mudah dijumpai. Pasien yang memiliki kesejahteraan spiritual dan sikap religius berpengaruh signifikan terhadap kepuasaan hidup, kedamaian dan kesehatan mental, dan juga mengurangi  kecemasan kematian. Koping spiritual dan religiusitas dapat mempengaruhi peningkatan kualitas hidup pasien paliatif dengan aktivitas spiritual Kata Kunci: Kesejahteraan Spiritual, Death Anxiety, Pasien Paliatif